Multilevel analysis of the determinants of smoking and second-hand smoke exposure in a tobacco-cultivating rural area of southwest China - Cai, Le (BMJ Publishing Group, 2013)
OBJECTIVES: To examine contextual and individual demographical predictors of smoking and exposure to second-hand smoke (SHS) in a tobacco-cultivating rural area of southwest China. METHODS: A cross-sectional survey of 4070 consenting individuals aged 18 years or more was conducted in 2010. Information on demographical characteristics, tobacco smoking status and SHS exposure were obtained by a standard questionnaire. Multilevel logistic regression was used to model the variation in prevalence of smoking and SHS exposure. RESULTS: In the study population, the prevalence rates of smoking and exposure to SHS were 63.5% and 74.7% for men, and 0.6% and 71.2% for women, respectively. Men were more likely to use tobacco than women: OR 8.27, 95% CI (4.83 to 10.97). Age was inversely associated with the probability of tobacco use (OR 0.98, 95% CI 0.97 to 0.99), and exposure to SHS (OR 0.97, 95% CI 0.96 to 0.99). Individual educational level was inversely associated with smoking, but showed no association with exposure to SHS. Adults who did not grow tobacco were less likely to consume tobacco (OR 0.75, 95% CI 0.57 to 0.99) and to be exposed to SHS (OR 0.76, 95% CI 0.58 to 0.99). Living in a high-income community was associated with a low rate of current smoking (OR 0.66, 95% CI 0.57 to 0.77) and SHS exposure (OR 0.58, 95% CI 0.52 to 0.65). CONCLUSIONS: Future interventions to reduce smoking and exposure to SHS in China should focus more on tobacco farmers, less-educated individuals and on poor rural communities.